2022
DOI: 10.3866/pku.whxb202206006
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Tungsten Carbide Coupled with Liquid-Phase Dye Photosensitizer for Efficient Photocatalytic Hydrogen Production

Abstract: Tungsten carbide (WC) is commonly used as a photocatalytic material for hydrogen production via water reduction. However, it is often combined with an effective photoabsorber to provide sufficient photoactivity. This is attributed to the narrow band gap of WC, which leads to an inadequate redox capability for water reduction. Notably, this limitation was overcome using a novel solid-liquid photocatalytic system that compliments bare WC photocatalysts with liquid-phase photosensitizing erythrosine B (ErB). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Currently, Erythrosin B(EB) sensitization has attracted much attention in H 2 evolution. Lei et al reported on a novel solid-liquid photocatalytic system that compliments tungsten carbide (WC) photocatalysts with liquid-phase photosensitizing EB; the hydrogen evolution rate reached 66 µmol/h, while pure WC showed poor activity (almost no H 2 generation) [44]. Zhang et al used EB as a sensitizer for Cu/g-C 3 N 4 photocatalytic hydrogen evolution and reached a rate that was 26 times higher than that of the non-sensitized system [45].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Erythrosin B(EB) sensitization has attracted much attention in H 2 evolution. Lei et al reported on a novel solid-liquid photocatalytic system that compliments tungsten carbide (WC) photocatalysts with liquid-phase photosensitizing EB; the hydrogen evolution rate reached 66 µmol/h, while pure WC showed poor activity (almost no H 2 generation) [44]. Zhang et al used EB as a sensitizer for Cu/g-C 3 N 4 photocatalytic hydrogen evolution and reached a rate that was 26 times higher than that of the non-sensitized system [45].…”
Section: Introductionmentioning
confidence: 99%
“…1 In response to this, photocatalytic technology that realizes hydrogen production from water enables a one-stop solution to both energy crisis and environmental protection. [2][3][4][5][6] Signicantly, graphite phase carbon nitride (g-C 3 N 4 , abbreviated as CN) with a two-dimensional lamellar structure is widely investigated as a photocatalytic material due to its suitable band gap structure, good physical and chemical stability, and high availability. 7 One major drawback of such material is associated with its relatively large band gap (2.7 eV) for very limited solar utilization.…”
mentioning
confidence: 99%